A study on software quality factors and metrics to enhance software quality assurance. (10th January 2020) - Kassie, Nigussu Bitew; Singh, Jagannath
The industries are giving more attention on software quality improvement and assessment, however the majority of researches has been done in the field of internal quality improvement. But, less attention has been given to the user's prospective to improve the quality of a software. The users want the best quality in the usability. The achievement of software companies totally relies upon the user's satisfaction. We focus on customer perspectives of software quality. In this article, first we present some of the existing software quality metrics and their uses. Then, we have accumulated most of the software quality metrics from the literature and prepared a bunch of 27 metrics. Then, we have conducted a survey, with our university students, on the user's perspective to rank the important software quality factors. Based on their responses, we have proposed a new quality model which is user's perspective quality model.